2018
DOI: 10.1016/j.molmet.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic regulation of VLDL receptor by PPARβ/δ and FGF21 modulates non-alcoholic fatty liver disease

Abstract: ObjectiveThe very low-density lipoprotein receptor (VLDLR) plays an important role in the development of hepatic steatosis. In this study, we investigated the role of Peroxisome Proliferator-Activated Receptor (PPAR)β/δ and fibroblast growth factor 21 (FGF21) in hepatic VLDLR regulation.MethodsStudies were conducted in wild-type and Pparβ/δ-null mice, primary mouse hepatocytes, human Huh-7 hepatocytes, and liver biopsies from control subjects and patients with moderate and severe hepatic steatosis.ResultsIncre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 53 publications
4
55
1
1
Order By: Relevance
“…This was accompanied by a decrease in the amount of VLDL receptors in humans. Decreased VLDL receptor levels were as well observed in PPAR-δ knocked-down primary mouse hepatocytes and in the liver of PPAR-δ null mice, confirming the observations in human [29]. Moreover, high-fat diet (HFD)-fed mice show as well decreased hepatic PPAR-δ mRNA levels, invigorating the outcome of the latter study [37].…”
Section: Dysregulation Of Ppars During Nashsupporting
confidence: 77%
See 1 more Smart Citation
“…This was accompanied by a decrease in the amount of VLDL receptors in humans. Decreased VLDL receptor levels were as well observed in PPAR-δ knocked-down primary mouse hepatocytes and in the liver of PPAR-δ null mice, confirming the observations in human [29]. Moreover, high-fat diet (HFD)-fed mice show as well decreased hepatic PPAR-δ mRNA levels, invigorating the outcome of the latter study [37].…”
Section: Dysregulation Of Ppars During Nashsupporting
confidence: 77%
“…Using PPAR-δ knockout mice, it could be demonstrated that PPAR-δ exhibits anti-atherogenic properties by reducing very-low density lipoproteins (VLDLs). This is also a consequence from FGF21 signaling [29], which also forms a link to PPAR-α [24,26]. PPAR-δ activation counters angiotensin II-induced adipocyte growth and lipid accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…In obese monkey, PPARβ/δ activation by the potent PPARβ/δ agonist GW501516 normalized serum insulin and TAG concentrations, decreased low-density lipoprotein cholesterol, and increased high-density lipoprotein cholesterol [49], which was also the case in diet-induced and genetically obese mice [50]. Although PPARβ/δ mediates the transcriptional response to native very low density lipoprotein (VLDL) in macrophage [51], Ppard-null mice were found to exhibit up-regulation of hepatic VLDL receptor due to activation of heme-regulated eukaryotic translation initiation factor 2α kinase and nuclear factor erythroid 2-related factor 2 [52].…”
Section: Role Of Pparβ/δ In the Livermentioning
confidence: 95%
“…Therefore, a major mechanism of tanshinol A alleviating liver injury is partially consensus with previous research in terms of regulating Aft4 ‐involved pathway (Wang et al, ) and enhancing capacity of antioxidation (Yang et al, ), and it is first time that hopylipidemic mechanisms of tanshinol A are found to be highly associated with upregulation of Atf4/Fgf21/Vldlr . Still, there are some tanshinol A‐leading mRNA expression alteration such as Angptl4 and Fgf21 , which are fasting‐induced adipose factor (Gonzalez‐Muniesa et al, ) and pathogenesis of hepatic steatosis (Zarei et al, ), respectively, do not show consensus to previous research, and this inconsistency may be characteristic pathogenesis for triton‐1339W‐induced hyperlipidemia and liver injury, and it is reversible after tanshinol A treatment. Preliminarily, our outcomes only will provide baseline insight (mRNA change) into further exploration of tanshinol A.…”
Section: Discussionmentioning
confidence: 95%